Campus Delft: History, policy framework and development of the TU Delft campus - van der Hoeven, Frank (project baikal, 2015)
The Delft University of Technology is adapting its campus to the challenges it faces in a rapidly-changing academic context. The original monofunctional greenfield area is being transformed into a high-quality urban campus. The campus needs to provide a sustainable learning and working environment for staff, students and visitors. This article outlines the historical background of the campus, the aims for its future development set out in the university’s policy framework, and the actions that stem from this.